Damage propagation in a masonry arch subjected to slow cyclic and dynamic loadings - J. Toti; V. Gattulli; Elio Sacco (Fracture and Structural Integrity)
In the present work, the damage propagation of a masonry arch induced by slow cyclic and dynamic loadings is studied. A two-dimensional model of the arch is proposed. A nonlocal damage-plastic constitutive law is adopted to reproduce the hysteretic characteristics of the masonry material, subjected to cyclic static loadings or to harmonic dynamic excitations. In particular, the adopted cohesive model is able to take into account different softening laws in tension and in compression, plastic strains, stiffness recovery and loss due to crack closure and reopening. The latter effect is an unavoidable feature for realistically reproducing hysteretic cycles. In the studied case, an inverse procedure is used to calibrate the model parameters. Then, nonlinear static and dynamic responses of the masonry arch are described together with damage propagation paths.